2007
DOI: 10.1007/s11277-007-9378-9
|View full text |Cite
|
Sign up to set email alerts
|

Adding Speech to Location-based Services

Abstract: The first generation of Location-based Services (LBSs) did not succeed on the market. In order to prepare LBSs of the next generation for the challenges of pervasive service execution in different situations (e.g. while walking on the street or while driving a car) the user interface must provide a second modality of interaction besides the visual interface. In this paper, we describe the challenges and a possible solution for combining LBSs with a spoken-dialogue user interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Nepper et al [5] suggested using speech for proactive (i.e. notrequested) execution of location-based services, for instance a tourist guide.…”
Section: Prior Workmentioning
confidence: 99%
“…Nepper et al [5] suggested using speech for proactive (i.e. notrequested) execution of location-based services, for instance a tourist guide.…”
Section: Prior Workmentioning
confidence: 99%